Spiral Density Waves in the Multiple-armed Galaxy NGC 628 - Jason C. Speights; Virginia Aust; Qinyan Lu (The Astrophysical Journal)
Radial profiles of pattern speeds are measured at subkiloparsec resolution for NGC 628. The radial profiles are directly measured using a general form of the Tremaine–Weinberg method that allows for the pattern speed to vary with radius. The method is applied to both stars and CO, H i , and H α spectral lines. The trends in the results are consistent for all of the data, showing that sources and sinks in the interstellar medium have a negligible effect when applying the integrated continuity equation. The spiral pattern rotates at a greater angular frequency in the inner region of the disks than in their outer region. Most of the measured values of the pattern speed are less than the material speed. The results for the inner disk show an approximately constant trend, consistent with rigidly rotating density waves. The offsets in stellar photometric and spectral line intensity data corroborate this result. There are radially decreasing trends in the results for the outer region of the disks that are similar to the material speed, consistent with shearing patterns or what is expected for overlapping wave modes of decreasing pattern speed. There is no single theory for the origin of the spiral patterns that can explain all of the results, but the results fail to provide evidence for a single global wave mode.